Profile of an occupation – roofer - Schambeck, Arne [Verfasser] (My University, 2021)
"Roofers do much more than roofing. They carry out other works on all areas of the roof and exterior walls of a building, and also install energy measures and solar thermal and photovoltaic systems. This description of the occupation explains the extent to which climate protection forms part of the training occupation. It also shows which trends are emerging and how trainee numbers are developing." (Author's abstract, BIBB-Doku)
Keywords: S 6.2.6 Hoch- und Tiefbauberufe; 370; Dachdecker; Berufsbilder